(untitled) (Altre Modernità, 2022)
In this paper, within the framework of Applied Linguistics and Critical Discourse Analysis, we will carry out a multilingual contrastive analysis of the speeches given by the political leaders of Spain, the United Kingdom, Italy, and Portugal at the beginning of 2020, when they announced tough measures to face the health crisis caused by COVID-19. Our initial hypothesis is that they will employ different linguistic resources to persuade the audience, since, at the beginning of the pandemic, political parties joined their forces to make citizens aware of the necessity of working together to face the crisis. The aim of our research is to use real samples of language to detect similarities and differences among the texts, as well as forms of persuasion and/or mass manipulation, and to observe if the sender’s ideology is manifested in the discourse. To do so, the research will be based on a qualitative study of the four discourses, but complemented with the data provided by Sketch Engine, which includes the words and collocations most used in each corpus. The results show that, except for some slight differences in the way they appeal to fear, in general the four speeches use similar persuasion techniques, as part of messages that appeal to patriotism, unity in the fight against the virus, and social responsibility.